AKSES PENYANDANG DISABILITAS TERHADAP PEKERJAAN: KAJIAN LITERATUR - Erissa, Dhea; Widinarsih, Dini (Jurnal Pembangunan Manusia, 2022)
According to data from the ILO, the International Labor Organization, 82 percent of people with disabilities in the world live in developing countries and live below the poverty line. They find it difficult to get various accesses including in the fields of employment, health, information, politics. Opportunities for persons with disabilities to find work are lower than those of non-disabled persons. This article discusses the access of persons with disabilities in Indonesia to work. The method used for this writing is a literature review through the Google Scholar database. From the results of the study, it is known that there have been efforts to provide access for persons with disabilities in the field of employment, but the level of participation of persons with disabilities is still there. This is due to, among other things, the low capacity of persons with disabilities, as well as the lack of access to information on time availability.